Answer: 1) (0,-3) 2) (4,-2) 3) (2,3) 4) (-2,2)
Step-by-step explanation: Hope this helps!
Answer:
Step-by-step explanation:
1 3^2 is =
subtract what u get from up here
boooooom
Well you are given the roots.
if we have 3 it would.have to be x^3. So something like:
y = ax^3 + bx^2 + cx + d
this could.also be written:
y = (x + a) (x + b) (x + c)
when you are able to write it like this, we know that the opposite of a, b, and c are roots. this is because if we can make any of the insides of the 3 parenthesis equal 0 then y = 0 and that x.is a root. Well if we know the 3 roots that x will be then we just have to figure out the a, b, and c. So let's plug our roots in.
y = (-1 + a) (-5 + b) (-3 + c)
now we have to make each parenthesis equal 0 to find what a, b, and c should be. It is obvious a = 1 to make.that one zero and b = 5 and c = 3. So we know a, b, and c. now let's plug.those into our first equation.
y = (x + 1) (x + 5) (x + 3)
this is your equation. You can multiply out if necessary
Answer:
Step-by-step explanation:
79+80+92+92+81+100+88+98+71+100+91+90
=1,062/12 = 88.5